Cost evaluation for Se(IV) removal, by applying common drinking water treatment processes: Coagulation/precipitation or adsorption. Issue 5 (October 2020) - Kalaitzidou, Kyriaki; Zouboulis, Anastasios; Mitrakas, Manassis
Abstract: This study provides a realistic estimation of uptake efficiency and operational cost for Se(IV) removal by the two most promising processes: coagulation/precipitation with iron salts and adsorption onto iron oxy-hydroxides granules. Removal efficiency at pH 7 and temperature 20 °C, corresponding to residual Se(IV) concentrations below the drinking water regulation limit 10 μg/L, was used to estimate the coagulant cost at approximately 357 €/kg Se(IV) removed, while the corresponding FeOOH cost, applying a single step adsorption process, was estimated at 2222 €/kg Se(IV) removed; however, the later was substantially decreased, and being lower than the coagulant treatment cost, when more than 5 adsorption/regeneration/reuse cycles were performed. Furthermore, the analysis of operational cost for a medium-scale drinking water plant, treating 100 m 3 /h with initial concentration 100 μg Se(IV)/L indicates that coagulation/precipitation process presents an operational cost of 104 €/10 3  m 3, which is more than twice lower than the application of a single adsorption step (being 236 €/10 3  m 3 ). Contrary, the operational cost of adsorption process is competitive to coagulation/precipitation process for treating 100 m 3 /h because of the lower energy and labor costs. The utilization of adsorbents on the commonly applied throwaway basis can be cost effective for an initial concentration below 30 μg Se(IV)/L, while for initial concentrations 50 and 100 μg/L the cost of adsorption is lower than coagulation's after 2 and 5 cycles of reuse, respectively. In conclusion, the scenario of adsorbent regeneration and reuse is necessary in order to narrow the cost gap between coagulation/precipitation and adsorption processes.